Comprehensive assessment of HF-rTMS treatment mechanism for post-stroke dysphagia in rats by integration of fecal metabolomics and 16S rRNA sequencing - Zhao, Fei; Chen, Jiemei; Shan, Yilong; Hong, Jiena; Ye, Qiuping; Dai, Yong; Hu, Jiahui; Zhang, Jiantao; Li, Chao; Wen, Hongmei (Frontiers in Cellular and Infection Microbiology, 2024)
Background The mechanism by which high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) improves swallowing function by regulating intestinal flora remains unexplored. We aimed to evaluate this using fecal metabolomics and 16S rRNA sequencing. Methods A Post-stroke dysphagia (PSD) rat model was established by middle cerebral artery occlusion. The magnetic stimulation group received HF-rTMS from the 7th day post-operation up to 14th day post-surgery. Swallowing function was assessed using a videofluoroscopic swallowing study (VFSS). Hematoxylin-eosin (H&E) staining was used to assess histopathological changes in the intestinal tissue. Intestinal flora levels were evaluated by sequencing the 16S rRNA V3-V4 region. Metabolite changes within the intestinal flora were evaluated by fecal metabolomics using liquid chromatography-tandem mass spectrometry. Results VFSS showed that the bolus area and pharyngeal bolus speed were significantly decreased in PSD rats, while the bolus area increased and pharyngeal transit time decreased after HF-rTMS administration (p < 0.05). In the PSD groups, H&E staining revealed damaged surface epithelial cells and disrupted cryptal glands, whereas HF-rTMS reinforced the integrity of the intestinal epithelial cells. 16S rRNA sequencing indicated that PSD can disturb the intestinal flora and its associated metabolites, whereas HF-rTMS can significantly regulate the composition of the intestinal microflora. Firmicutes and Lactobacillus abundances were lower in the PSD group than in the baseline group at the phylum and genus levels, respectively; however, both increased after HF-rTMS administration. Levels of ceramides (Cer), free fatty acids (FA), phosphatidylethanolamine (PE), triacylglycerol (TAG), and sulfoquinovosyl diacylglycerol were increased in the PSD group. The Cer, FA, and DG levels decreased after HF-rTMS treatment, whereas the TAG levels increased. Peptococcaceae was negatively correlated with Cer, Streptococcus was negatively correlated with DG, and Acutalibacter was positively correlated with FA and Cer. However, these changes were effectively restored by HF-rTMS, resulting in recovery from dysphagia. Conclusion These findings suggest a synergistic role for the gut microbiota and fecal metabolites in the development of PSD and the therapeutic mechanisms underlying HF-rTMS.